How much can we reduce delivery-related medical costs associated with maternal mortality? A nationwide cohort study from 2003 to 2021 - Nam, Jin Young (Frontiers in Public Health, 2025)
ObjectiveThis study aims to examine the association between maternal mortality and childbirth-related medical costs using both unadjusted and adjusted models and to assess the potential reduction in delivery-related medical costs associated with maternal mortality in South Korea.MethodsThis retrospective cohort study used data from the National Health Insurance Service Delivery Cohort Database of South Korea. A total of 7,171,578 participants were included. The outcome measured was delivery-related medical costs associated with maternal mortality. A Generalized Estimating Equation model with a log link and gamma distribution was used to estimate delivery-related medical costs.ResultsThe maternal death rates were 9.7 per 100,000 births. The adjusted mean delivery-related medical costs were approximately six times higher in cases with maternal death than in those without (2,802 vs. 480, p < 0.0001). The total delivery-related medical costs for all women with maternal mortality were approximately 2 million, accounting for 0.06% of total delivery-related medical costs. Although this proportion is relatively small, 83% of the direct medical costs associated with maternal mortality among South Korean women were potentially reducible.ConclusionThis study found that maternal mortality is associated with significantly higher delivery-related medical costs, nearly six times those of non-maternal mortality cases. Therefore, policymakers should consider reducing costs and improving maternal health outcomes, expanding access to prenatal care for early risk detection and strengthen nationwide maternal health monitoring systems.